Impact of COVID-19 Response on the HIV Epidemic in Men Who Have Sex With Men in San Francisco County: The Importance of Rapid Return to Normalcy. (15th April 2023) - Liang, Citina; Suen, Sze-chuan; Nguyen, Anthony; Moucheraud, Corrina; Hsu, Ling; Holloway, Ian W.; Charlebois, Edwin D.; Steward, Wayne T.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: In response to the COVID-19 pandemic, San Francisco County (SFC) had to shift many nonemergency health care resources to COVID-19, reducing HIV control resources. We sought to quantify COVID-19 effects on HIV burden among men who have sex with men (MSM) as SFC returns to pre-COVID service levels and progresses toward the Ending the HIV Epidemic (EHE) goals. Setting: Microsimulation model of MSM in SFC tracking HIV progression and treatment. Methods: Scenario analysis where services affected by COVID-19 [testing, care engagement, pre-exposure prophylaxis (PrEP) uptake, and retention] return to pre-COVID levels by the end of 2022 or 2025, compared against a counterfactual where COVID-19 changes never occurred. We also examined scenarios where resources are prioritized to reach new patients or retain of existing patients from 2023 to 2025 before all services return to pre-COVID levels. Results: The annual number of MSM prescribed PrEP, newly acquired HIV, newly diagnosed, and achieving viral load suppression (VLS) rebound quickly after HIV care returns to pre-COVID levels. However, COVID-19 service disruptions result in measurable reductions in cumulative PrEP use, VLS person-years, incidence, and an increase in deaths over the 2020–2035 period. The burden is statistically significantly larger if these effects end in 2025 instead of 2022. Prioritizing HIV care/prevention initiation over retention results in more person-years of PrEP but less VLS person-years and more deaths, influencing EHE PrEP outcomes. Conclusions: Earlier HIV care return to pre-COVID levels results in lower cumulative HIV burdens. Resource prioritization decisions may differentially affect different EHE goals.